Access to justice for minors in rape cases - Chávez Matos, Ana María (2024)
The immediate and timely statement of the aggrieved minors for sexual violence is transcendental in the prosecution of the crime carried out by the Public Prosecutor's Office. The reception in Gesell camera, due to the fact that it is an anticipated evidence, has the objective of individualizing the perpetrator. It must be carried out avoiding the revictimization of the aggrieved minor and with unrestricted respect for the right of technical defense of the person to identify himself in the respective statement that, in this case, will be represented by the Public Defense to guarantee the legality of the diligence and the due process. The pronouncement of the jurisdictional organ before the prosecutor's request for the anticipated evidence of a minor victim of rape must be resolved with a constitutional perspective. Priority must be given to the right to effective protection, the principle of the best interest of the child, the right to the truth and the condition of vulnerability, so that the holder of the criminal action can promptly obtain information regarding the perpetrator and objectively initiate the prosecution of the crime. On the contrary, the aggrieved minor receives from the judicial system a response of lack of protection as a victim and, due to the passage of time, the circumstances and details of the traumatic event are allowed to be forgotten, which the victim unconsciously rejects so that it does not remain in his or her memory. The conditioning of the formal requirements determined in the domestic legal system for the performance of the anticipated evidence in underage victims of serious crimes such as rape must be overcome through the application of international conventions and treaties to which we have adhered as a State party for its compliance and respect.